Web marketing in agri-food industry: Challenges and opportunities. (September 2020) - Caiazza, Rosa; Bigliardi, Barbara
Abstract: Background: Non-technological innovations in marketing are key drivers of competitive advantage of agri-food companies. The progressive and incessant affirmation of the Internet in the world economic panorama imposes the overcoming of the traditional models of marketing. The agri-food companies, in this new context, must think of themselves in the first place, mainly as a provider of information, and must be aware that it is facing a new type of customer, which becomes an active element of the marketing process. In recent years, agri-food companies have started processes of adaptation of their strategic and operational marketing activities with the aim of progressively integrating digital systems and exploiting their potential. Scope and approach: The aim of our paper is to analyze the relevance of innovations in marketing for agri-food companies starting from a literature review of web marketing. Specifically, our review is based on a database of over 700 articles from marketing and business journals, covering a period of over 20 years. It goes from the first web marketing publications of the last century to the most recent writings. The review examines the internet marketing literature in order to determine how it has evolved and to provide a comprehensive model useful to evidence the relevance of non-technological innovation for agri-food companies. Key findings and conclusions: Based on these results, we developed a comprehensive model including all the main aspects related to web marketing. Theoretical model has been then contextualized in the food industry, in order to understand how web marketing works in such a context. Some key examples are described in order to provide practical evidence.